Lower Extremity Reconstruction with the Anterolateral Thigh Flap - Nosrati, Naveed; Chao, Albert H.; Chang, David W.; Yu, Peirong (Journal of Reconstructive Microsurgery, 2012)
The versatility and location of the anterolateral thigh (ALT) flap make it well suited for lower extremity reconstruction. The purpose of this study was to evaluate surgical and functional outcomes by specific anatomic regions in the lower extremity to better define the role of the ALT flap in lower extremity reconstruction. A retrospective review of patients undergoing lower extremity reconstruction with an ALT flap between July 2002 and December 2010 was performed. Total 46 patients underwent lower extremity reconstruction with an ALT flap, of whom 29 (63%) had a pedicled flap and 17 (37%) a microvascular free flap. Defects were located in the hip/buttocks (n = 8), groin (n = 13), thigh (n = 8), knee (n = 5), leg (n = 6), and foot/ankle (n = 6). The mean postoperative follow-up was 4 months. Total flap loss occurred in two patients (4%). There were 11 recipient site complications (24%). The most common complication was recipient site seroma, which occurred in five patients (11%), all of whom had hip/buttock or groin defects. Overall, 38 patients (83%) returned to their preoperative functional status. The ALT flap is an effective method of lower extremity reconstruction. It can be performed as a pedicled or free flap, with good surgical and functional outcomes.
Keywords: reconstruction; ALT flap; lower extremity